Dampak Program Makan Bergizi Gratis (MBG) terhadap Saham Sub-Sektor Fish, Meat, Poultry di Bursa Efek Indonesia - Alwi Ihsan Nababan; Berry Dhiyashavana; Farianita Lestari; Devana Anisha Indra Putri (CV. ITTC INDONESIA, 2025)
Government policies often play a crucial role in shaping market sentiment and influencing investor behavior, especially in emerging capital markets. This study examines how Indonesia's Free Nutritious Meal Program (MBG), announced in 2024–2025, affected stock performance in the Fish, Meat, and Poultry sub-sector listed on the Indonesia Stock Exchange (IDX). Using an event study approach with a 10-day observation window (t-5 to t+4, where t0 is the official announcement date), we applied the Kolmogorov-Smirnov normality test and Wilcoxon Signed Rank Test to evaluate changes in Abnormal Return (AR), Trading Volume Activity (TVA), and Abnormal Trading Volume Activity (ATVA).Results show that abnormal returns remained relatively stable with a mean of -0.002805 before the event and -0.000361 after (p-value = 0.680 > 0.05), indicating no statistically significant change. Similarly, TVA and ATVA showed no abnormal patterns (p-value = 0.159 > 0.05). These findings suggest that the MBG announcement did not contain sufficient information content to trigger a significant short-term market reaction, reflecting semi-strong form market efficiency in Indonesia's capital market. Investors appear to perceive the program's direct impact on equity values as limited or delayed, with potential effects realized only in the long term.